Opportunity of durian seed flour as an alternative to commercial wheat flour - Hidayat, Jefri Pandu; Robiandi, Fadli; Arisalwadi, Meidi; Hariyadi, Asful (Journal of Agritechnology and Food Processing, 2022)
The  high carbohydrate content  in  durian seed flour  (DSF) has the potential to be a source of food energy that can replace wheat flour in the world. DSF processing has an impact on color changes that affect  the quality of the product.  Therefore, the purpose of this study is to modify durian seeds to obtain the best properties of durian seed flour through the soaking process. The modification was carried out  in a 0.6%  (w/v)  solution of sodium metabisulfite at a temperature of 30 ºC with a drying  temperature of 50 ºC for 17 hours before grinding and sifting in a size of 80 mesh.   Treatment of immersion time variables in minutes (40, 60, 80, 100, 120) using the Complete Randomized Design (RAL) method with three attempts.  The flour is then being analyzed its physical  and chemical properties.  The best treatment was obtained at soaking time during 120 minutes which had an impact on changes in chemical and physical properties.  The test  results showed that the longer soaking time reduced the moisture content and ash content of durian seed flour, but partially improved the  other parameters tested.  The amount of DSA, DSM  and fat is less affected by soaking time. In conclusion, DSF has the potential to be used as a base for pastries or biscuits due to its low water and protein content.  In addition, based on the residual content of sulfite, the durian seed flour obtained in this study is safe for consumption in accordance with GSFA standards.